Bacterial effluxome as a barrier against antimicrobial agents: structural biology aspects and drug targeting. Issue 4 (2nd October 2022) - Brindangnanam, Pownraj; Sawant, Ajit Ramesh; Prashanth, K.; Coumar, Mohane Selvaraj
ABSTRACT: Antimicrobial resistance (AMR) is fast becoming a medical crisis affecting the entire global population. The bacterial membrane is the first layer of defense for the bacteria against antimicrobial agents (AMA), specifically transporters in the membrane efflux these AMA out of the bacteria and plays a significant role in the AMR development. Understanding the structure and the functions of these efflux transporters is essential to overcome AMR. This review discusses efflux transporters (primary, secondary, and tripartite), their domain architectures, substrate specificities, and efflux pump inhibitors (EPI). Special emphasis on nosocomial ESKAPEE ( Enterococcus faecium., Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli ) pathogens, their multidrug efflux targets and inhibitors are discussed. Deep knowledge about the functioning of efflux pumps and their structural aspects will open up opportunities for developing new EPI, which could be used along with AMA as combination therapy to overcome the emerging AMR crisis.